Literature Research: The Use of Science, Technology, Engineering and Math (STEM) In Physics Learning - Norlaili Norlaili; Aqil Muhammad Al Huda; Hadma Yuliani; Nadia Azizah (Universitas Lambung Mangkurat, 2022)
The STEM approach is an approach that trains to understand the four aspects of it. The four aspects are science, technology, engineering and mathematics. However, the application of this approach is still not optimally developed in the learning process. This study aims to find out the advantages of the STEM approach and the obstacles in learning physics. The method to reach the purpose is literature research. The study reviewed various STEM research journals on physics studies published in the last ten years indexed in Sinta or National Proceedings. The number of journals used is 30 journals. The results showed that the use of STEM has the most advantages in improving student learning outcomes, while the most constraints in STEM learning are in adjusting STEM learning to the curriculum and the need for good time management. The results of this study can be used as input for physics teachers to apply the STEM approach in the physics learning process in the classroom.